Identification of Carotid Artery Microstructure and Plaque Rupture Using C-Arm Cone-Beam CT: A Case Report - Dong, Jia; Bai, Xuesong; Dmytriw, Adam A.; Xuan, Lanlan; Wang, Tao; Lu, Xia; Feng, Yao; Jiao, Liqun (Frontiers in Neurology, 2021)
C-arm cone-beam computed tomography (CBCT) offers a high imaging resolution with a wide range of contrast to visualize vessels, soft tissue, and bone. We report the usefulness of CBCT in observing neovascularization, microcalcification, and plaque rupture. A 56-year-old man presented with vertigo and complain of an unsteady gait for 5 months. Catheter angiography demonstrated right severe carotid stenosis with irregular filling defect, which on high-resolution MRI showed vessel wall enhancement. The CBCT showed high density structures and linear contrast enhancement from the vascular lumen to the plaque, related to microstructure and plaque rupture. Carotid endarterectomy was performed, and histopathology confirmed that the high-density areas represented neovascularization and microcalcification, with linear enhancement representing plaque rupture. This is the first report showing that microcalcifications and plaque rupture can be identified by CBCT. Thus, CBCT can be used as a promising supplement to current imaging modalities to evaluate plaque components more accurately.